Development of a new high-yield integration site assay reveals disease-specific patterns across HTLV-1-associated pathologies - Vincent Guiraud; Jérôme Alexandre Denis; Sofia Ben Attia; Erwan Ablin; Ronan Legrand; Véronique Morel; Claire Lacan; Sylvain Choquet; Rabab Debs; Margaux Cheval; Cindy Marques; Alexandre Le Joncour; et al. (Microbiology Spectrum)
ABSTRACT Human T lymphotropic virus type 1 (HTLV-1) chronic infection is maintained through mitotic proliferation of the infected CD4+ T cells, where the viral genome is integrated as a provirus in its host genome. HTLV-1 integration sites (ISs) have a part in HTLV-1-associated pathologies, with distinct IS patterns associated with malignant proliferation or inflammatory diseases. However, IS determination remains challenging because most assays rely on complex biological and biocomputing protocols. We present an IS assay that solely relies on PCR and Sanger sequencing, which allowed HTLV-1 IS determination in four patients with various HTLV-1-associated pathologies. We adapted an IS assay derived from a panhandle PCR, with several modifications to increase yield. Absence of bias regarding IS retrieval was confirmed using TCRγ clonality. IS analysis was performed in four HTLV-1-positive patients: two with polymyositis, one with adult T-cell leukemia/lymphoma (ATLL), and one with HTLV-1-associated myelopathy (HAM). Overall yield was around 20%, with a mean sequence length downstream the IS of 336 ± 230 bp (range, 44–1,024 bp). There was no major bias in clonal determination, as IS results matched clonality assessed using a TCRγ assay. The IS assay revealed distinct clonal patterns depending on HTLV-1 pathology: dominated by a large clone for ATLL, oligo- or polyclonal for polymyositis and polyclonal for HAM. As a conclusion, we present an easy-to-implement integration site assay for HTLV-1 that allows a relatively unbiased IS analysis regarding clonal populations. This assay could be useful to further explore IS involvement in HTLV-1 associated pathologies.IMPORTANCEHuman T lymphotropic virus type 1 (HTLV-1) chronic infection is due to the mitotic proliferation of infected CD4+ T cells, where the proviral DNA is integrated in its host DNA. HTLV-1 integration seems to play a non-negligible part in HTLV-1-associated pathologies. However, most HTLV-1 integration studies originate from a few centers, mostly because integration site (IS) protocols rely on high-cost experimental materials and advanced bioinformatic analysis. We have developed an IS assay that solely relies on Taq polymerase and Sanger sequencing, with no need for costly biological material nor complex bioinformatic skills. This assay was successfully performed on four HTLV-1-positive patients with distinct pathologies (ATLL, HAM, and polymyositis) and distinct material (blood and cerebrospinal fluid). All four patients originated from distinct areas in Africa and the Caribbean Sea Island. This assay has a relatively high yield, around 20%. It provided similar results regarding HTLV-1 clonality compared with a TCRγ assessment, which indicated that IS recovery was likely unbiased.